Variabilidade genética em procedências e progênies de Dipteryx alata vogel para fins de conservação genética e produção de sementes - Gonzalez Zaruma, Darlin Ulises [UNESP]; De Oliveira Canuto, Daniela Silvia [UNESP]; Pupin, Silvelise [UNESP]; Cambuim, José [UNESP]; Da Silva, Alexandre Marques [UNESP]; Mori, Edson Seizo [UNESP]; Sebbenn, Alexandre Magno; De Moraes, Mario Luiz Teixeira [UNESP] (My University, 2015)
Dipteryx alata is a tree species with high economic potential, because of the quality of its timber, fruits and almonds, which provide food for wild animals and humans. The species occurs naturally in the Cerrado, but due to human settlement, natural populations have been fragmented. Thus, it is necessary to make efforts oriented to the ex situ conservation of the remaining populations. This study aimed to evaluate the genetic variability in a provenance and progenies experiment of D. alata, aged nine years, installed on Selvíria-MS. For this purpose, seeds of 48 trees in Campina Verde (MG), 17 in Itarumã (GO) and 41 Brasilândia (MS) were collected. The trial was established in a randomized block design with six plants per plot and five replications. The traits height (H), diameter at breast height (DBH), average crown diameter (DMC) and stem form (FOR) were measured. It has been found that trees show a good development and are adapted to the local conditions of the test. By analyzing the likelihood ratio test, significant differences were detected at the provenances and progenies levels for all traits analyzed, which means good chances of success for selection in breeding programs. DBH was the most suitable trait for selection. The selection strategy within progenies (thinning 33.3% of the plants) led gains of 12.6%, causing a loss of only 9% of the initial genetic diversity.
Genetic variability in the provenance and progeny Dipteryx alata vogel for conservation genetics and seed production purposes
Keywords: Baru; Cerrado; Ex situ conservation; Genetic gain